Tiga Mekanisme Perampasan Sumber Daya Alam di Konawe Utara: Pembalakan, Perkebunan Sawit, dan Pertambangan Nikel dalam Perspektif Ekologi Politik - Sarlan Adijaya; Danial; Zainal; Laxmi; Raemon; La Ode Aris; Aghista Febriani (PT PUSTAKA CENDEKIA GROUP, 2026)
This article analyzes three sequential and mutually reinforcing mechanisms of natural resource dispossession occurring in North Konawe Regency, Southeast Sulawesi: (1) forest exploitation through Forest Concession Rights (HPH) by PT. Intisixta since 1992; (2) forest conversion for oil palm plantations by at least six companies since 1996; and (3) open-pit nickel ore mining conducted by 56 active Mining Business Permit (IUP) holders. Using a political ecology framework, this article argues that these three mechanisms are not separate events but rather a structured regime of accumulation that can be understood as accumulation by dispossession, systematically transferring resources from the indigenous Culambacu and Tolaki communities to capitalist actors. The integrative literature review is strengthened by field data and analysis of licensing documents. The findings reveal that cumulative deforestation reached at least 30,369 hectares between 1997–2013; 19,005 hectares of forest areas were converted into oil palm plantations; 42,871 hectares of land were controlled by mining concessions; and the poverty rate remained above the national average (13.53%) despite massive natural resource exploitation. The article concludes that persistent poverty amid abundant natural resources reflects a structural, rather than incidental, failure of governance.